MORPHOLOGICAL AND MOLECULAR EVIDENCE IN THE DELIMITATION OF BEHRIA AND BESSERA, TWO GENERA OF THE MILLA COMPLEX (THEMIDACEAE) - ETELVINA GÁNDARA (Boletín de la Sociedad Botánica de México, 2009)
Among the taxa of the Milla complex (Themidaceae), a monocot group of perennial petaloid geophytes, there are two genera with controversial taxonomic status: Behria and Bessera. Tree-based and character-based analyses were conducted on 14 populations to determine if they should be considered different taxa. In addition, ecological separation was taken into account. As outgroups representative taxa of Dandya, Jaimehintonia, Milla and Petronymphe, i.e. the rest of the genera in the Milla clade, were used. Behria is a monotypic genus restricted to Baja California and Bessera includes two species from the Pacific slopes of Mexico and the Trans-Mexican Volcanic Belt. The chloroplast intergenic spacer psbK-psbI was sequenced and 37 morphological characters were coded. Tree-based analyses retrieved all populations of Behria and all populations of Bessera as monophyletic groups, both forming part of a more inclusive clade. Character-based analysis detected six diagnostic characters, all of which were fl oral. The conclusion of recognizing Behria and Bessera as independent genera was based on these results and also on their different distributional ranges.